2010
DOI: 10.1111/j.1551-2916.2009.03396.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Room Temperature Photoluminescence of Mesoporous Zirconia with a Tetragonal Nanocrystalline Framework

Abstract: Mesoporous ZrO2 with a tetragonal (t) nanocrystalline framework was synthesized using zirconium propoxide as the zirconium precursor and cetyltrimethylammonium bromide as pore‐directing agent and subsequent calcination of the inorganic/organic intermediate. The Raman spectrum showed six distinct peaks at 146, 268, 325, 480, 615, and 645 cm−1, which further confirm t‐structure of the mesoporous ZrO2. Fourier transform infrared spectroscopy analysis reveals that mesoporous ZrO2 prepared at 500°C is template free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…PL spectra depend strongly on the particle size, defects and impurities present in the materials. The PL properties of ZrO 2 nanostructures have been studied extensively by the scientific community [21][22][23], however, the role of particle size along with the crystal phases of ZrO 2 nanostructures is not addressed yet systematically. Harrison et al [24] had reported that the luminescent centers constituted by Zr 4+ ions in an asymmetric site surrounded by the oxygen ions are mainly responsible for emission peak.…”
Section: Pl Spectroscopymentioning
confidence: 99%
“…PL spectra depend strongly on the particle size, defects and impurities present in the materials. The PL properties of ZrO 2 nanostructures have been studied extensively by the scientific community [21][22][23], however, the role of particle size along with the crystal phases of ZrO 2 nanostructures is not addressed yet systematically. Harrison et al [24] had reported that the luminescent centers constituted by Zr 4+ ions in an asymmetric site surrounded by the oxygen ions are mainly responsible for emission peak.…”
Section: Pl Spectroscopymentioning
confidence: 99%
“…In the past decade, multiple applications of zirconia (ZrO 2 ), that including solid-oxide fuel cells [1][2][3], oxygen sensors [1][2][3], catalysts [1][2][3][4] and supports for catalysts [5,6], have received a keen interest. High hardness [5], high melting-point, excellent chemical inertness [7], low thermal conductivity, ionic conductivity [5], high corrosion resistance, high dielectric constant (j) value [8][9][10] and amphoteric behavior [11] are among the properties, which recommend it as a functional metal oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, metal oxide nanoparticles, such as silica (SiO 2 ) [11][12][13], titanium dioxide (TiO 2 ) [14][15][16][17], cerium dioxide (CeO 2 ) [18][19][20], zirconium dioxide (ZrO 2 ) [21,22], and variants of these [23], are of particular relevance to catalytic chemistry, semiconductors, and drug delivery. Porous metal oxide nano-or micro-spheres with dimension-controlled morphology possess unique properties that are especially suited to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods exist by which to obtain these structures, including hydrothermal, sol-gel, and self-assembly methods, and combinations of these. However, these methods generally involve complex multistep 4 operations and long reaction times (several hours) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]27,28]. Recently, sizeand morphology-controlled inorganic-organic hybrid metal and metal oxide nanoparticles have been synthesized in supercritical fluids.…”
Section: Introductionmentioning
confidence: 99%